Evidence of a dual histogenetic pathway of sacrococcygeal teratomas. Issue 2 (10th October 2016) - Emerson, Robert E; Kao, Chia‐Sui; Eble, John N; Grignon, David J; Wang, Mingsheng; Zhang, Shaobo; Wang, Xiaoyan; Fan, Rong; Masterson, Timothy A; Roth, Lawrence M; Cheng, Liang
Abstract : Aims: Sacrococcygeal teratomas are rare tumours that occur most frequently in neonates, although adult cases also occur. The molecular pathogenesis of these tumours and their long‐term prognosis is uncertain. We investigated the i(12p) status of a large number of primary sacrococcygeal teratomas in both children and adults, including cases with malignant germ cell tumour elements. Methods and results: Fifty‐four sacrococcygeal teratoma specimens from 52 patients were identified, and available follow‐up information was obtained. Fluorescence in‐situ hybridization analysis was performed to identify isochromosome 12p [i(12p)] abnormalities on paraffin blocks of the tumours. Among the 48 paediatric patients, there were 44 teratomas and four tumours with combined teratoma and yolk sac tumour (one of whom also had primitive neuroectodermal tumour). The teratomas included 37 mature teratomas and 11 immature teratomas (four grade 1, two grade 2, and five grade 3). The 44 teratomas lacking a yolk sac tumour component were all negative for i(12p). The four tumours with a yolk sac tumour component were all positive for i(12p). The four adult cases all lacked non‐teratomatous germ cell tumour components, immature elements, and i(12p). Follow‐up information was available for 32 patients. Two patients with teratoma had recurrence, but were alive with no evidence of disease after long‐term follow‐up. One patient with combined teratoma and yolk sac tumour had recurrence 7 months after resection. The other patients were alive with no evidence of disease at last follow‐up. Conclusions: Our data suggest that paediatric sacrococcygeal teratomas should be considered as two distinct groups with divergent histogenetic pathways. The prognosis of these tumours is excellent, despite rare recurrence.